THE CONCEPT OF THE INTEGRATION OF SCIENCE AND FAITH IN THE THOUGHT OF BADIUZZAMAN SAID NURSI AND ITS CONTRIBUTION TO MODERN ISLAMIC EDUCATION STRATEGIES - Achmad Fachrurozi Aminusyai; Nunung Hidayati (Academic Bright Collaboration, 2026)
This study aims to examine the concept of the integration of knowledge and faith in the thought of Badiuzzaman Said Nursi and to analyse its contribution to modern Islamic educational strategies. This study is motivated by the tendency to separate science and faith in Islamic educational practice. Consequently, the thought of Badiuzzaman Said Nursi is considered relevant as it offers an integrative approach that utilises science as a means to strengthen faith. This study employs a qualitative approach using library research methods. Data was obtained through an analysis of Badiuzzaman Said Nursi’s works in Indonesian, as well as various supporting literature such as books, academic articles, and relevant previous research. The research findings indicate that, according to Badiuzzaman Said Nursi, knowledge and faith are two complementary and inseparable elements. This concept contributes to modern Islamic educational strategies through the strengthening of the spiritual dimension within the curriculum, a learning approach based on ayat kauniyah, and the development of students’ character to be rational, faithful, and of good moral character. This research, particularly in Indonesia, has applied the ideas of Badiuzzaman Said Nursi. Examples include studies at the Faculty of Tarbiyah, UIN Sunan Kalijaga, and the Nursemesta Foundation. This research offers an integrative perspective that can serve as the foundation for a holistic Islamic educational strategy, one that is adaptive to scientific developments yet remains rooted in the values of faith.